Nghiên cứu chế tạo vật liệu polyme compozit từ hệ nhựa epoxy/DDS gia cường sợi thủy tinh có mặt vi sợi xenlulo. Phần 4. Ảnh hưởng của vi sợi xenlulo hình thành do vi khuẩn đến tính chất cơ học và độ bền mỏi của vật liệu polyme compozit từ nhựa epoxy - Đức, Vũ Minh; Minh Ngọc, Phan Thị; Lánh, Phạm Thị; Yến Oanh, Đoàn Thị; Đô, Ngô Huy (Vietnam Journal of Chemistry, 2015)
The aim of this study is to investigate the influence of bacterial cellulose (BC) content on the damage mechanisms of glass fibers reinforced epoxy under fatigue loading cycles and some other mechanical properties. Specimens were manufactured from prepregs to keep exact glass fibers/epoxy ratio. The mechanical properties of the materials such as tensile strength, flexible strength were affected slightly by the adding of BC. The fatigue life, however, increased significantly for 0.3% BC content of glass fibers reinforced epoxy. Scanning electron microscopy-analysis revealed the different deformation of the matrix due to the BC.